Medical Terminology for Healthcare Professions - Nelson, Andrea M.; Greene, Katherine (Open textbook library., 2021)
Medical Terminology for Healthcare Professions is an Open Educational Resource (OER) that focuses on breaking down, pronouncing, and learning the meaning of medical terms within the context of anatomy and physiology. This resource is targeted for Healthcare Administration, Health Sciences, and Pre-Professional students.